Identification and Characterization of Csa-miR395s Reveal Their Involvements in Fruit Expansion and Abiotic Stresses in Cucumber - Lu, Lin; Luo, Weirong; Yu, Wenjin; Zhou, Junguo; Wang, Xinfa; Sun, Yongdong (Frontiers in Plant Science, 2022)
The miR395 plays an indispensable role in biochemical processes by regulating their target genes. However, little is known about the roles of miR395 in cucumber fruit expansion and response to abiotic stresses. Here, 4 Csa-miR395s and 8 corresponding target genes were identified in the cucumber genome. Csa-miR395s were all located on the same chromosome (Chr 5). Csa-miR395a/b/c and Csa-miR395d were distributed in different branches without a closer genetic relationship. Massive cis-acting elements, including light, phytohormone, and stress response elements, were detected in the promoter regions of Csa-MIR395s, indicating that Csa-miR395s might be involved in complex regulatory networks to control cucumber growth and development and stress response. In addition, Csa-miR395a/b/c shared the same target genes, and Csa-miR395d had its specific target genes. Tissue-specific expression analysis showed that Csa-miR395a/b/c were all expressed in the leaf, root, ovary, and expanded fruit of cucumber and highly expressed in the expanded fruits compared to the ovary, while Csa2G215520 and Csa1G502860 (target genes of Csa-miR395a/b/c) presented a downregulated trend in the expanded fruit compared to the ovary. Meanwhile, the protein co-expression network revealed that these target genes had interactions in sulfur metabolism. These results suggested that Csa-miR395a/b/c targeting Csa2G215520 and Csa1G502860 might promote cucumber fruit expansion by affecting sulfur metabolism. Additionally, Quantitative Real-time PCR analysis validated that Csa-miR395s could be regulated by NaCl stress, and Csa-miR395a/b/c could respond to PEG stress, which further confirmed the reliability of cis-acting elements data. Taken together, our results could be helpful for further exploration of the functions of miR395s in cucumber fruit expansion and response to abiotic stresses.